Analisis Pengaruh Geometri Peledakan Terhadap Fragmentasi Hasil Peledakan Limestone Pada PT. Semen Padang, Kota Padang. - Laju Boy Ardi Harahap; Dedi - Yulhendra (Departemen Teknik Pertambangan FT UNP, 2021)
This final project is based on the fragmentation of limestone blasting resulting in a size of ≥ 80 cm which hinders the performance of the crusher. The purpose of this final project is to get a blasting geometry recommendation; to achieve a fragmentation value of ≥ 80 cm with a retained percentage of 10%. Actual blasting geometry with blast hole diameter 4 inches, burden 3,05 m, spacing 3,04 m, blast hole depth 7,59 m, subdrilling 0 m, PC 4,35 m, stemming 3,24 m, ladder height 7,59 m and PF value 0,60 kg / m3. The percentage of rock fragmentation resulting from blasting in the actual geometry uses a split desktop with the percentage of fragmentation ≥ 80 cm retained, namely 21,605%. The geometries that have a major influence on the actual blasting result fragmentation are; Burden with (R2) = 0,7705 or 77,05%, Space with R²) = 0,7495 or 74,95% and PF with (R²) = 0,6356 or 63,56 %. Therefore, the author tries to propose a blasting geometry so that the resulting fragmentation can fulfill the policies that have been made and the non-uniformity of blasting fragmentation results can be better. The proposed geometry uses the RLAsh formula with the proposed burden of 2,5 m, spacing of 3,5 m, height of 7,5 m, PC 5,75 m, stemming 2,5 m, subdrilling 0,75 m, blast hole depth 8,25 m and PF 0,85 kg/m3. Based on the proposed geometry improvement, the percentage retained by rock fragmentation with predictions using the Kuz-Ram method is obtained, the percentage retained by fragmentation is ≥ 80 cm, which is 5,8%.